Penelitian Retrospektif Profil Klinikopatologi Tumor Kelenjar Liur di Instalasi Patologi Anatomi RSUD Dr. Saiful Anwar Malang Periode Tahun 2017-2021 - Lukman Firmansyah, Muhammad; Fadli, Muhammad; Retnani, Diah (RSUD Dr. Saiful Anwar Province of East Java, 2023)
Abstract Background: Cases of salivary gland tumors are relatively rare. There are not many data that explain the prevalence of salivary gland tumor incidence in Indonesia. Objective: This study aims to determine the clinicopathological profile of salivary gland tumors based on case incidence, age, gender, location and histopathological subtype at the Anatomical Pathology Installation of Dr. Saiful Anwar Hospital Malang in 2017-2021. Methods: This research is a quantitative descriptive study. Data was collected from medical records from 2017 to 2021 at the Anatomical Pathology Installation of Saiful Anwar Hospital, Malang. All subjects in this study were all clinical data of patients with tumor located salivary gland (parotid, submandibular, sublingual/cavum oris). Results and Discussion: There were 162 cases of salivary gland tumors from 2017-2021, malignant neoplasm 57 (35%), benign neoplasm 60 (37%) and non neoplasm 45 (28%). The distribution of the incidence of cases per year is not the same and does not always increase. There was a relationship between the increase in cases of malignancy with increasing age. There is no relationship between increasing cases of salivary gland tumors and malignancy with gender. The most common locations for salivary gland tumors and malignant neoplasm in parotid gland. The most malignant neoplasm is mucoepidermoid carcinoma 11 (19.2%), the most benign neoplasm is pleomorphic adenoma 38 (63.3%), the most non-neoplastic cases is inflammation and abscess 34 (75.5%). Conclusion: Salivary gland tumors are rare cases. Cases of malignancy increase in adults and the elderly. The most common location in the parotid gland with the most cases of malignant neoplasm is mucoepidermoid carcinoma and the most benign neoplasms is pleomorphic adenoma. Keywords: Salivary gland tumor, histopathology.